First detection of the rare hydrogen sulfide isotopologue: The pure rotational and ?2 bands of HD33S; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 232 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Sydow C. Christian; Bauerecker S. Sigurd (2019, 2019)
Title screen